Relação entre a remuneração do conselho de administração e a frequência de seus membros às reuniões - Luiz, Jane Marusa Nunes (Universidade do Vale do Rio dos Sinos, 2018)
The purpose of this study is to empirically investigate the attendance of direcors at meetings and their effects on board compensation of Brazilian companies listed on BM&FBOVESPA, from 2015 to 2016. To achieve this research, a comprehensive set of variables was tested considering the arguments of agency theory and previous literature, using multiple linear regression. The results indicate that the size of the board and the number of busy direct affect negatively the compensation, while board independence, participation in committees, age and graduation are positively associated with compensation of the board of directors. It has also been found that there is a relationship between size, profitability and the shareholding control of the company with the board compensation. It was also identified that the percentage of board members' attendance is approximately 93%, and which are held around 12 annual meetings, however, the effort of the board of directors, as measured by the frequency and number of meetings, showed no significance statistical analysis to explain the compensation. These findings provide implications for future researches into the performance of directors in monitoring the management and compensation of the board of directors and executives.
Keywords: Teoria de agência; Conselho de administração; Frequência nas reuniões; Remuneração do conselho; Agency theory; Board of directors; Meeting attendance; Board compensation; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis